Методика множественно-формального представления предметной области аудита - Нескородева, Т. В. (НТУ "ХПИ", 2014)
Предложена методика множественно-формального представления предметной области аудита для комплексного анализа по следующим направлениям: поставка, производство, продажа, финансово-экономическая деятельность; уровням и периодам управления; видам хозяйственной деятельности, средств и источников предприятия; по соответствию нормативных, плановых и отчетных данных. Методика проиллюстрирована на примере учета прямых материальных затрат.

The method of multiple-formal representation of the audit domain for a comprehensive analysis of the following areas: types of work (supply, production, sales, financial and economic activities); The structure of the analysis domain is presented as a union of sets of data on the direction considered and determined the relationship between the data sets. The method is illustrated by the account of direct material costs in the calculation of the production cost. Converting data analytical account of direct material costs in the calculation of cost of production is formalized as a multilayer directed graph whose vertices – analytical account of the account of current assets, ribs – accounting transactions of material costs. Transmission, storage, data conversion is performed according to the structure of the graph and at all stages shown in the domain analysis of the relevant departments and activities.
Method of multiple-formal representation audit domain
Keywords: экономика; аудит; множественно-формальное представление; предметная область аудита; комплексный анализ; материальные затраты; учет затрат; multiple-formal representation; subject area of audit; comprehensive analysis; account of the direct material costs